A importância da integração universidade e serviços de saúde - Lima, Daniela Pereira [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Saliba, Nemre Adas [UNESP] (My University, 2010)
Brazilian Curricular Directrix demand changes on teaching dental surgeon, proposing new scenes of learning and study other than the classroom. So, pedagogic projects should search for integral and adequate education by relating teaching, research and extension/assistance. This paper discusses the importance of university extension activities on teaching Odontology students and relates the experience of Araçatuba Dental School of São Paulo State University. This school develops some university extension activities since the 60s by Dental Service Beyond School (SEMO, in portuguese). Among the activities included by SEMO there are several projects, such as: “Program of Dental Attention for Pregnant Women”, “Program of Dental Attention to Juvenile Foundation at Araçatuba”, “Always Smiling – Health Promotion for Institutionalized Elderlies”, “Santa Clara de Assis Nursery School Program of Dental Attention”, and "Promotion of oral health in Araçatuba public kindergarten schools”. These programs give the student knowledge of structure dimensions of public health services; chance to participate on attendance for the population, comprehension of oral health politics, and the role of dental surgeon in social context, where these students will work in the future. The positive impact obtained with these services is perceived by students return. Most of them feel satisfied about the experience lived there.

Las Directrices Curriculares Nacionales exigen mudanzas en la formación del cirujanodentista, proponiendo nuevos escenarios de estudio que van más allá de la sala de clases. Para ese propósito, los proyectos pedagógico visan contemplar la formación integral y adecuada del académico, esto, por medio de la articulación entre enseñanza , pesquisa y extensión/asistencial. Este artículo discute la importancia de de la extensión universitaria en la formación del alumno de grado en Odontología y narra la experiencia de la Facultad de Odontología de Araçatuba (FOA) – UNESP. Desde la década del 60 la FOA – UNESP desarrolla actividades de Extensión Universitaria y Servicio Extramuro Odontológico (SEMO). Entre las actividades contempladas están:” Programa de Atención Odontológica a la Gestante”, “Programa de Atención Odontológica al Adolescente” (Fundación Mirim), Proyecto” Siempre Sonriendo- Promoción de salud para ancianos institucionalizados”, “Programa de Atención Odontológica a los Niños” (Creche Santa Clara de Assis), y “Promoción de Salud Bucal en las Escuelas Municipales de Educación Infantil de Araçatuba”, proporcionando así, al alumno, el conocimiento de la estructura de los servicios públicos de salud, participación en el atendimiento a la población, comprensión de las políticas de salud bucal, como también, el papel del cirujano-dentista en el contexto social en el que, el académico, irá a ingresar. El impacto positivo obtenido con estos servicios a través del SEMO es captado por medio de la satisfacción del trabajo vivenciado por los alumnos en el último año del grado.

As Diretrizes Curriculares Nacionais exigem mudanças na formação do cirurgião-dentista, propondo novos cenários de estudo que vão além da sala de aula. Para tanto, os projetos pedagógicos devem contemplar a busca pela formação integral e adequada do acadêmico, por meio da articulação entre o ensino, a pesquisa e extensão/assistência. Este artigo discute a importância das atividades de extensão universitária na formação do aluno de graduação em Odontologia e relata a experiência da Faculdade de Odontologia de Araçatuba (FOA) - UNESP. A FOA - UNESP desde a década de 60 desenvolve atividades de Extensão Universitária e também de Serviço Extramuro Odontológico (SEMO). Dentre as atividades contempladas estão o “Programa de Atenção Odontológica à Gestante”, o Programa de Atenção Odontológica a adolescentes (Fundação Mirim), o projeto “Sempre Sorrindo - Promoção de Saúde para Idosos Institucionalizados”, Programa de Atenção Odontológica às crianças (Creche Santa Clara de Assis), e o projeto “Promoção de saúde bucal nas escolas municipais de educação infantil de Araçatuba”, proporcionando ao aluno o conhecimento das dimensões estruturais dos serviços públicos de saúde, a participação no atendimento à população, a compreensão das políticas de saúde bucal, bem como do papel do cirurgião-dentista no contexto social no qual futuramente o acadêmico irá ingressar. O impacto positivo obtido com estes serviços através do SEMO é percebido por meio da satisfação dos alunos quanto à experiência vivenciada no último ano de sua graduação.
The importance of integration between university and health services
La importancia de la integración de la universidad y los servicios de salud
Keywords: Human resources; Single Health System; Dental education; Recursos humanos; Sistema Único de Salud; Educación Odontológica; Recursos humanos; Sistema Único de Saúde; Educação em odontologia